ANALYSIS OF THE SCHOOL LITERACY MOVEMENT AT SD NEGERI 138 PEKANBARU - Gorby Sergeyevich Muhammad Rasyid; Emisliana (Yayasan Thaifah Manshurah Pekanbaru, 2023)
The purpose this study was to describe how the implementation pf the deep school literacy movement at SD Negeri 138 Pekanbaru. This research was conducted at SD Negeri 138 Pekanbaru in the 2022/2023 school year. This research uses a descriptive qualitative method with with a case study approach. The data sources in this study were obtained from observations of the implementation of the school literacy movement program, interviews with several informants, namely teachers, students, and librarians, as well as documentation. The results showed that the school literacy movement program at SDN 138 Pekanbaru was carried out in three stages, namely the habituation stage, the development stage, and the learning stage. At the habituation stage carried out are morning pick-up activities, literacy habituation activities every Wednesday, recitation activities in class and activities to sing obligatory/regional songs. At the development stage, what is done is to develop students' reading comprehension skills through readings that students do for 15 minutes and read them in their own language. The learning stage carried out is the use of enrichment books in lessons accompanied by student work. Furthermore, the supporting facilities at SD Negeri 138 Pekanbaru are quite complete to support the implementation of the school literacy movement program.